2017
DOI: 10.1016/j.cub.2016.12.043
|View full text |Cite
|
Sign up to set email alerts
|

Shortening of Microtubule Overlap Regions Defines Membrane Delivery Sites during Plant Cytokinesis

Abstract: SummaryDifferent from animal cells that divide by constriction of the cortex inwards, cells of land plants divide by initiating a new cell wall segment from their centre. For this, a disk-shaped, membrane-enclosed precursor termed the cell plate is formed that radially expands towards the parental cell wall [1][2][3]. The synthesis of the plate starts with the fusion of vesicles into a tubulo-vesicular network [4][5][6]. Vesicles are putatively delivered to the division plane by transport along microtubules of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
44
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 43 publications
(45 citation statements)
references
References 42 publications
1
44
0
Order By: Relevance
“…Comparing the signal distribution with GFP-POK2, we noticed that the signal of GFP-POK2 (1-589) at the phragmoplast midzone appeared wider (Figs 4G and EV1E and G, Appendix Fig S2A). Therefore, we quantified the average full width half maximum (FWHM) [40] of both signals at the midzone and confirmed that the distribution of GFP-POK2 (1-589) is considerably broader than GFP-POK2, while the phragmoplast size remains equal ( Fig 4H and I).…”
Section: Pok2 Midzone Association Requires Fine-tuningsupporting
confidence: 56%
“…Comparing the signal distribution with GFP-POK2, we noticed that the signal of GFP-POK2 (1-589) at the phragmoplast midzone appeared wider (Figs 4G and EV1E and G, Appendix Fig S2A). Therefore, we quantified the average full width half maximum (FWHM) [40] of both signals at the midzone and confirmed that the distribution of GFP-POK2 (1-589) is considerably broader than GFP-POK2, while the phragmoplast size remains equal ( Fig 4H and I).…”
Section: Pok2 Midzone Association Requires Fine-tuningsupporting
confidence: 56%
“…The interaction between CLASP and PRC1 suggests that a similar mechanism is present in animal cells (Liu et al, 2009). In higher eukaryotes kinesin-4 regulates the dynamics of microtubule overlaps additionally (Kurasawa et al, 2004;Bieling et al, 2007;Hu et al, 2011;de Keijzer et al, 2017). When overlap length decreases, the decrease in kinesin-4 will induce extra microtubule growth.…”
Section: Regulation Of Catastrophesmentioning
confidence: 99%
“…In the later stages of the animal spindle and in the plant phragmoplast, a regular array of short antiparallel overlaps is necessary for successful cytokinesis (Mollinari et al, 2002;Vernì et al, 2004;Zhu and Jiang, 2004;Hu et al, 2011;Kong et al, 2015;de Keijzer et al, 2017). The site of cytokinesis is directly linked to the site of overlaps.…”
Section: Function Of Antiparallel Overlapsmentioning
confidence: 99%
See 2 more Smart Citations